Determinants of academic performance of student-workers in higher education - Lopes, Ana Sofia (2018)
Although in recent years access to higher education in Portugal has expanded, there are still some people who interrupt their academic progression and enter the labour market not because of lack of skills but because of monetary constraints. Thus, returning to school is considered of great importance to mitigate this discrimination and reinforce workers’ qualification. Even though the determinants of academic performance have been deeply studied, the different characteristics, the lack of time and the multiple motivations of student-workers justify them to receive an independent treatment. Therefore, based on an extended set of observed attributes, which account for individual, degree and, for the first time to our knowledge, job characteristics, we develop two regression models to find the main determinants of the academic performance (measured by the final grade point average and by the completion time) of student-workers in higher education. We use a longitudinal dataset constituted by 332 student-workers that have enrolled in an undergraduate program at Leiria Polytechnic Institute (IPLeiria) in 2008 or 2009 and have completed it until 2015. The data was obtained by matching an internal dataset of IPLeiria with data from the Ministry of Education and Science, Portugal. The results show that student-workers who finish their degrees behave similarly to the non-worker students in their academic performance, but with different determinants explaining it. Parents’ education has a negative effect on final grade whereas higher previous qualifications, peer effects, better integration and higher average grades withindegree increase academic performance. The access regime and the field of study are also relevant, as well as self-employment, job-degree relation, private/public nature of the employer, and whether or not the job is qualified. We expect that our work contributes to develop policies that improve the success of student-workers and therefore increase the participation of workers in higher education.